(untitled) (The Insight, 2026)
Background: Gestational Diabetes Mellitus (GDM) is a well-known complication in which spontaneous hyperglycemia develops during pregnancy. Insulin resistance is the key pathophysiological mechanism of GDM. The aim of this study was to assess the association of Insulin-Like Growth Factor-I (IGF-I) in maternal serum as a Predictor of GDM. Methods & Materials: Prospective cohort study was conducted in the Department of Obstetrics & Gynecology, Dhaka Medical College Hospital, Dhaka, Bangladesh during December 2020 to November 2021. Results: The age, parity and BMI of study population were not statistically significant (p>0.05) when compared with Insulin–Like Growth Factor-I. The mean serum Insulin –Like Growth Factor-I was significantly higher in patients with GDM than non GDM (387.4±110.5 vs 254.1±73.8 ng/ml). ROC analysis of Insulin –Like Growth Factor-I to predict GDM among the pregnant women found an AUC value of 0.875 (95% CI, 0.763-0.986) which was statistically significant (p<0.001). A cut-off value of ≥352.1 showed the highest youden index (0.771) with 85.7% sensitivity and 91.4% specificity, 90.5% accuracy, 63.2% PPV and 97.4% NPV. Increased serum Insulin –Like Growth Factor-I was found in 12(85.7%) in GDM group and 7(8.6%) in non GDM group with RR 24.0, 95% CI (5.86-98.31%). The difference was statistically significant (p<0.05) between GDM and non GDM groups. Conclusion: These findings revealed that increased maternal serum Insulin –Like Growth Factor-I at 8-12 weeks of gestation is associated with subsequent development of GDM. Elevated maternal serum Insulin –Like Growth Factor-I at 8-12 weeks of gestation can be used as a biomarker for prediction of GDM.